Pengaruh Model Pembelajaran Berbasis Tim terhadap Kemampuan Berpikir Kritis Mahasiswa Pendidikan Agama Kristen - Barbara Green Winslet Bessie; Harun Y Natonis (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2025)
Critical thinking skills are fundamental to everyday life and academics, allowing individuals to analyze information, evaluate arguments, and draw evidence-based conclusions. In the context of Christian Religious Education (PAK), critical thinking also has a theological dimension, where reason, as a divine gift, is renewed through Christ to understand divine truth and love God. Given this urgency, this study aims to explore how the implementation of the Team Based Learning (TBL) Model can improve the critical thinking skills of PAK students. This study uses a descriptive qualitative method through literature study, collecting and analyzing data from various journal articles and books. The results show that the TBL structure includes individual preparation, team discussion (IRAT/GRAT), problem-based concept application, and peer feedback and evaluation systematically encourage high-level cognitive processes. In conclusion, TBL has proven effective in improving the critical thinking skills of PAK students, while deepening their understanding of the material and their religious competence.